Tourism and Commodification Of Malay Cultural Arts in the Industrial Revolution 4.0 Era - Suryadi (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2020)
The Industrial Revolution 4.0 will bring a fundamental transformation to Malay arts and culture, which at the same time will certainly bring changes to the identity or identity of the supporting community. In this era that is increasingly digital, virtual and connected beyond physical boundaries and is increasingly virtual, the physical and communal character of Malay art and cultural performances may be eroded. Only with careful planning and synergistic cooperation between various parties (stakeholders/artists, academics, government, tourism actors, computer technology experts, etc.), Malay arts and culture will continue to be alive, useful economically, but still have a positive value in the framework of strengthening the identity of the Malay people. The commodification of Malay art and culture in particular and Indonesia in general in an all-virtual world in the future will only be beneficial, not only economically but more importantly for one's own identity, if the level of education of the Indonesian nation also increases evenly, a 'condition' for someone to do not experience 'shock culture' and tend to deify everything that is foreign and belittle one's own. Keywords: tourism; commodification; art; culture; Malay; RI4.0